MicroRNAs, Long Non-Coding RNAs, and Circular RNAs in the Redox Control of Cell Senescence - Daniele Lettieri-Barbato; Katia Aquilano; Carolina Punziano; Giuseppina Minopoli; Raffaella Faraonio (Antioxidants, 2022)
Cell senescence is critical in diverse aspects of organism life. It is involved in tissue development and homeostasis, as well as in tumor suppression. Consequently, it is tightly integrated with basic physiological processes during life. On the other hand, senescence is gradually being considered as a major contributor of organismal aging and age-related diseases. Increased oxidative stress is one of the main risk factors for cellular damages, and thus a driver of senescence. In fact, there is an intimate link between cell senescence and response to different types of cellular stress. Oxidative stress occurs when the production of reactive oxygen species/reactive nitrogen species (ROS/RNS) is not adequately detoxified by the antioxidant defense systems. Non-coding RNAs are endogenous transcripts that govern gene regulatory networks, thus impacting both physiological and pathological events. Among these molecules, microRNAs, long non-coding RNAs, and more recently circular RNAs are considered crucial mediators of almost all cellular processes, including those implicated in oxidative stress responses. Here, we will describe recent data on the link between ROS/RNS-induced senescence and the current knowledge on the role of non-coding RNAs in the senescence program.